EDUKASI â€œMY HOME MY LABâ€ PEMBELAJARAN PRAKTIKUM BAGI GURU IPA DI KABUPATEN BEKASI SEBAGAI ALTERNATIF PRAKTIKUM PADA MASA PANDEMI - Suryanda, Ade; Azrai, Eka Putri; Rini, Daniar Setyo; Fitriani, Anisa; Aprida, Naurah; Izzatunnisa, Lita (Al-Khidmat : Jurnal Ilmiah Pengabdian Kepada masyarakat, 2022)
Experiment in science learning is a necessity. Experiment will provide students with very meaningful knowledge and experience. The Covid-19 pandemic that occurred in Indonesia required the world of education to implement an online learning model from March 2020 until today. Therefore, an effective Experiment learning strategy is needed during this pandemic. This service activity is based on the fact that there are still many obstacles that science teachers encounter in carrying out practical learning activities, as part of science learning activities. The general purpose of this activity is to increase the knowledge and skills of science teachers in conducting science Experiment activities during the pandemic, by utilizing facilities, materials and tools that are easily accessible at home by students. This training uses the experiential learning method with a participant-centered approach through case study techniques, and simulations. The resulting output targets are an increase in the understanding and knowledge of teachers about science Experiment, an increase in the ability to create science Experiment activities at home using facilities, materials and tools that are easily obtained by students and the potential for teachers to make science Experiment s at home with the slogan "MY HOME MY LABORATORY". This activity has been successfully carried out, providing supplies to science teachers, so they are ready to carry out practical activities even though they are still in a pandemic condition, by utilizing their homes and facilities as student laboratories.